Restoration of Innate and Adaptive Immune Responses by HCV Viral Inhibition with an Induction Approach Using Natural Interferon-Beta in Chronic Hepatitis C - Y. Kishida; N. Imaizumi; H. Tanimura; Y. Haruna; S. Kashiwamura; T. Kashiwagi (Clinical and Developmental Immunology)
Chronic hepatitis C (CHC) is a serious medical problem necessitating more effective treatment. This study investigated the hypothesis that an induction approach with nIFN-beta for 24 weeks followed by PEG-IFN-alpha+ribavirin (standard of care: SOC) for 48 weeks (novel combination treatment: NCT) would increase the initial virologic response rate and restore innate and adaptive immune responses in CHC. Seven CHC patients with a high viral load and genotype 1b were treated with NCT. Serum cytokine and chemokine levels were evaluated during NCT. NCT prevented viral escape and breakthrough resulting in persistent viral clearance of HCVRNA. IL-15 was increased at the end of induction therapy in both early virologic responders (EAVRs) and late virologic responders (LAVRs); CXCL-8, CXCL-10, and CCL-4 levels were significantly decreased (𝑃<0.05) in EAVR but not in LAVR during NCT, and IL-12 increased significantly (𝑃<0.05) and CXCL-8 decreased significantly (𝑃<0.05) after the end of NCT in EAVR but not in LAVR. NCT prevented viral breakthrough with viral clearance leading to improvement of innate and adaptive immunity resulting in a sustained virologic response (SVR). NCT (𝑛=8) achieved a higher SVR rate than SOC (𝑛=8) in difficult-to-treat CHC patients with genotype 1 and high viral loads.